2020
DOI: 10.1002/smll.201907146
|View full text |Cite
|
Sign up to set email alerts
|

Cu2MoS4/Au Heterostructures with Enhanced Catalase‐Like Activity and Photoconversion Efficiency for Primary/Metastatic Tumors Eradication by Phototherapy‐Induced Immunotherapy

Abstract: Photoimmunotherapy can not only effectively ablate the primary tumor but also trigger strong antitumor immune responses against metastatic tumors by inducing immunogenic cell death. Herein, Cu2MoS4 (CMS)/Au heterostructures are constructed by depositing plasmonic Au nanoparticles onto CMS nanosheets, which exhibit enhanced absorption in near‐infrared (NIR) region due to the newly formed mid‐gap state across the Fermi level based on the hybridization between Au 5d orbitals and S 3p orbitals, thus resulting in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 102 publications
(68 citation statements)
references
References 60 publications
(58 reference statements)
0
68
0
Order By: Relevance
“…[ 127 ] In our group, plasmonic Cu 2 MoS 4 (CMS)/Au heterostructures were fabricated by depositing Au nanoparticles onto 2D CMS nanosheets ( Figure a). [ 6 ] Because of the hybridization of Au 5d and S 3p orbitals, a midgap state across the Fermi energy appeared, which dramatically decreased the energy bandgap of the electron transition, thus resulting in a more prominent PTT/PDT effect than pure CMS (Figure 13b,c). Moreover, we proved that CMS/Au‐based phototherapy could effectively inhibit cancer metastasis via phototherapy‐induced immunotherapy (Figure 13d).…”
Section: Htt‐based Multipronged Approaches In Synergistic Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…[ 127 ] In our group, plasmonic Cu 2 MoS 4 (CMS)/Au heterostructures were fabricated by depositing Au nanoparticles onto 2D CMS nanosheets ( Figure a). [ 6 ] Because of the hybridization of Au 5d and S 3p orbitals, a midgap state across the Fermi energy appeared, which dramatically decreased the energy bandgap of the electron transition, thus resulting in a more prominent PTT/PDT effect than pure CMS (Figure 13b,c). Moreover, we proved that CMS/Au‐based phototherapy could effectively inhibit cancer metastasis via phototherapy‐induced immunotherapy (Figure 13d).…”
Section: Htt‐based Multipronged Approaches In Synergistic Immunotherapymentioning
confidence: 99%
“…[ 4 ] Thus, innovative and effective cancer treatments with remarkably improved therapeutic effects and reduced side effects are urgently needed. [ 5–7 ] Hyperthermia therapy (HTT), a treatment where the targeted tumor sites reach temperatures within a range of 41–48 °C, has been applied as an adjuvant cancer treatment strategy to improve the therapeutic effect of chemoradiotherapy. [ 8 ] More importantly, hyperthermia therapy has a direct cancer cell killing effect.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, an increase in CD8 T cell and DC activity was also observed in both mouse spleens and tumors. Chang et al [26] synthesized a Cu 2 MoS 4 /Au heterostructure as a theranostic agent and showed that it could also stimulate an antitumor immune response. Under NIR irradiation, tumor-bearing mice had higher activations of both CD4 and CD8 T cells in mouse spleens in treatment groups as well as an increase in IL-6, IL-12, and TNF-α in mouse serum.…”
Section: Photothermal Therapymentioning
confidence: 99%
“…In 2018 the Nobel Prize in Physiology or Medicine was awarded to the field of cancer for the discovery of cancer therapy by inhibition of negative immune regulation (Hokland et al, 2018 ). The purpose of immunotherapy is to use the body's own immune system to stimulate and activate systemic immune response, specifically eliminate minimal residual disease, resulting in inhibiting tumor growth and breaking the immune tolerance (Shekarian et al, 2015 ; Hu et al, 2019b ; Chang et al, 2020 ). In other ways, tumor immunotherapy is to overcome the mechanism of tumor immune escape, so as to re-awake immune cells to clear cancer cells.…”
Section: Introductionmentioning
confidence: 99%